Sistem Informasi Pengelompokan Pembayaran Denda Tilang Menggunakan Algoritma K-Means Clustering - Nana Suarna; Nining Rahaningsih; Nana Mulyanasari; Usup Supendi (Ma'soem University, 2021)
This study Violation can be defined as a situation where there is a mismatch between the rules and implementation. The regulation is contained in Law Number 22 Year 2009, concerning